2016
DOI: 10.1111/jam.13045
|View full text |Cite
|
Sign up to set email alerts
|

The cocoa bean fermentation process: from ecosystem analysis to starter culture development

Abstract: Summary Cocoa bean fermentation is still a spontaneous curing process to facilitate drying of nongerminating cocoa beans by pulp removal as well as to stimulate colour and flavour development of fermented dry cocoa beans. As it is carried out on farm, cocoa bean fermentation is subjected to various agricultural and operational practices and hence fermented dry cocoa beans of variable quality are obtained. Spontaneous cocoa bean fermentations carried out with care for approximate four days are characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
266
3
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(298 citation statements)
references
References 67 publications
14
266
3
15
Order By: Relevance
“…The results showed that the different processing conditions influenced the composition and activity of the microbial communities as well as metabolite accumulation in the endosperms. In addition, the current findings corroborate the effect of microorganisms on the chemical profiles of coffee beans and support the idea of using a starter culture during coffee processing for improved process control and prevention of spoilage and eventually steering the sensory differentiation of roasted coffee, as has been performed for cocoa bean fermentation (62,63). Further studies should ultimately allow strengthening of the understanding of the impact of the microbiota on coffee cup quality and provide robust data for the development of commercial starter cultures.…”
Section: Discussionsupporting
confidence: 67%
“…The results showed that the different processing conditions influenced the composition and activity of the microbial communities as well as metabolite accumulation in the endosperms. In addition, the current findings corroborate the effect of microorganisms on the chemical profiles of coffee beans and support the idea of using a starter culture during coffee processing for improved process control and prevention of spoilage and eventually steering the sensory differentiation of roasted coffee, as has been performed for cocoa bean fermentation (62,63). Further studies should ultimately allow strengthening of the understanding of the impact of the microbiota on coffee cup quality and provide robust data for the development of commercial starter cultures.…”
Section: Discussionsupporting
confidence: 67%
“…However, only two phases, the main fermentation phase and the maturation phase, characterize the lambic beer production process carried out in a common brewery, whereby AAB are only isolated sporadically. Although LAB and yeasts are predominant in lambic beers, as they are in most other naturally fermented foods and beverages, these acidic beers are thus characterized by the presence of complex microbial communities . The most prevalent and functional microorganisms during lambic beer fermentation and maturation are highlighted below in their order of appearance.…”
Section: Lambic Beersmentioning
confidence: 99%
“…80,81 They have an optimal growth temperature between 20 and 35 ∘ C. They are Crabtree-positive yeasts, which is part of a make-accumulate-consume strategy. 68,[82][83][84] This allows them to dominate the early stages of food and beverage fermentation processes in general, because of their quick conversion of the available carbohydrates via pyruvate into ethanol through alcoholic fermentation (necessary for redox balancing or the recuperation of NAD + from NADH + H + produced during the EMP pathway) during the make-accumulate phase. Alcoholization impairs the growth of competing microorganisms by fast consumption of the substrates available and the production of high ethanol concentrations.…”
Section: Saccharomyces Speciesmentioning
confidence: 99%
“…Subsequently, LAB degrades the carbohydrate-rich pulp producing mainly lactic acid, finally, AAB transforms the lactic acid into acetic acid (3, 4). In this last step, the production of acetic acid lowers pH and increases bean mass temperature (40-50 °C), these conditions affect the seed and cause its death, promoting the subsequent release of the flavor precursors associated with chocolate quality (57). Microorganisms are also responsible for the production of volatile compounds related to aromatic flavor (e.g., alcohols, organic acids, esters, and aldehydes) and the removal of compounds associated with bitterness and astringency (e.g., like tannins, polyphenols) (1, 3, 8).…”
Section: Introductionmentioning
confidence: 99%